Analysis on selection of building materials to reduce energy consumption in commercial buildings - Ong, Zi Yang (2019)
The purpose of this study is to analyze current building materials used in current commercial buildings in Singapore and its energy consumption, as well as explore alternative green building materials in green buildings and their potential energy consumption savings. Using these findings, this report also aims to propose initiatives that can be implemented to increase awareness on green building materials amongst builders, developers and owners, as well as to incentivize usage of green building materials to reduce overall energy consumptions of future commercial buildings. For the design of this project, we first identified current existing materials used for Singapore’s commercial buildings and their energy consumption level. The methodology used to compute energy consumption was via the Energy Use Intensity (EUI) index. The EUI index is a measurement of total amount of energy consumed by a particular building in a span of one year, measured in terms of kilo watt hour per gross floor area (kWh/m²). After which, we explored current green buildings materials used in Singapore and their EUI. Comparing the EUI for current building materials and green materials, we then verified the potential energy consumption savings, and proposed material selection for future construction work for commercial buildings, as well as initiatives to incentivize usage of green buildings and improve current Building Construction Authority (BCA) schemes. Analysis of our results suggest that commercial buildings with green materials, paired with latest technology systems are able to achieve higher potential energy savings. Proposed green materials for future construction work includes Superior Innovative Coating Concepts (SICC) coatings, Cool Roof and Biowall. The research analysis on the Singapore construction landscape and current BCA schemes such as the BCA Green Mark, suggest a need to improve awareness of benefits of green materials amongst developers, and improvements in BCA scorecards to incentivize adoption of these materials. In conclusion, there is strong evidence that selecting green materials can significantly reduce energy consumption levels in commercial buildings in Singapore compared to current materials. Thus, we recommend a two-prong approach to encourage the adoption of these materials, through educating builders on the existence and benefits of our identified green materials, as well as incentivizing them through structural changes in current BCA accreditation schemes.